2019
DOI: 10.26715/rjds.11_1_5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude about tobacco use among school personnel in Bangalore South-a Cross Sectional Study.

Abstract: Background: Tobacco use is so addictive among youth and is one of the global epidemics which require constant monitoring and timely appropriate action to prevent usage. School personnel play one of the main roles in taking appropriate action. Aim: To assess knowledge and attitude of tobacco use pattern among school personnel in Bangalore city. Material and Methods: A cross sectional study was carried out for a period of six months from May to October 2017. Stratified cluster sampling was done to include the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Majority of the teachers reported that they did not use any form of smoked and smokeless tobacco, similar to Bhat et al, Alnasir et al and Kwamanga et al [11][12][13] The knowledge and attitude of the teacher in the government and private schools about tobacco harm was adequate. Most agreed that smoke from other people's cigarettes is harmful to 9,11,14,15 Article 8 of the FCTC is the protection from second hand smoke. 10 Article 14 of FCTC is related to "offer" of MPOWER and teachers can play a pivotal role in offering tobacco cessation as counsellor.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Majority of the teachers reported that they did not use any form of smoked and smokeless tobacco, similar to Bhat et al, Alnasir et al and Kwamanga et al [11][12][13] The knowledge and attitude of the teacher in the government and private schools about tobacco harm was adequate. Most agreed that smoke from other people's cigarettes is harmful to 9,11,14,15 Article 8 of the FCTC is the protection from second hand smoke. 10 Article 14 of FCTC is related to "offer" of MPOWER and teachers can play a pivotal role in offering tobacco cessation as counsellor.…”
Section: Resultssupporting
confidence: 71%
“…10 The need for specific training to be able to teach students to avoid or stop using tobacco was reported higher than Bhat et al, Irimie et al, Kaleta et al and GSPS India 2006 and 2009. 9,11,19,20 Only one fifth responded that they had received training to prevent tobacco use among youth which well translated by the demand of orientation and training programs. This was reported lower than GSPS India 2006 and 2009 survey.…”
Section: Resultsmentioning
confidence: 99%
“…9 Study by Bhat et al showed that majority (88.2%) of school staff were aware of harmful effects of SHS. 8 Female participants in the study reported more avoidance to SHS compared to male teachers. A study by Nagler et al revealed more prevalence of smoking among male teachers compared to female teachers in India.…”
Section: Discussionmentioning
confidence: 78%
“…A study conducted by Bhat et al among school teachers in Bangalore revealed that majority of school children did not use any forms of tobacco and though they were aware of the addictive effect of tobacco, they did not perceive second hand smoke as harmful. 8 This calls for understanding the knowledge and behaviour of high school teachers towards second hand smoke exposure so that proper educational programs can be designed to raise awareness among school teachers thereby helping them to create a favourable attitude among their adolescent students towards avoidance of second-hand smoke exposure and tobacco cessation. Since there is lack of literature determining the knowledge and behaviour of school teachers towards second hand smoke exposure, a cross sectional survey is planned to assess the knowledge and behaviour of high school teachers towards second hand smoke exposure in Davanagere city.…”
Section: Introductionmentioning
confidence: 99%